Solving scheduling problems in a multi-stage multi-product batch pharmaceutical industry - Kopanos, Georgios (2010)
An iterative two-stage decomposition solution strategy for solving real-world scheduling problems in multi-stage multi-product batch plants is presented. The proposed method has as a core a mixed integer mathematical model, and consists of a constructive step, wherein a feasible and good solution is rapidly generated by following some insertion criteria, and an improvement step, wherein the initial solution is systematically enhanced by adopting several rescheduling techniques. The proposed strategy performance is tested on a number of problem instances of a complicated real-world multi-stage multi-product pharmaceuticals scheduling problem. High quality solutions are reported within reasonable computational time.